2010
DOI: 10.1021/tx1001767
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of an LC-MS/MS Method for the Detection of the Vinyl Chloride-Induced DNA Adduct N2,3-Ethenoguanine in Tissues of Adult and Weanling Rats Following Exposure to [13C2]-VC

Abstract: In the 1970s exposure to vinyl chloride (VC) was shown to cause liver angiosarcoma in VC workers. We have developed a new LC-MS/MS method for analyzing the promutagenic DNA adduct N2,3-ethenoguanine (εG) and have applied this to DNA from tissues of both adult and weanling rats exposed to 1100 ppm [13C2]-VC for 5 days or 1100 ppm VC for 1 day. This assay utilizes neutral thermal hydrolysis and an HPLC clean-up prior to quantitation by LC-MS/MS. The number of endogenous and exogenous εG adducts in DNA from tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 40 publications
2
24
0
Order By: Relevance
“…While endogenous εG was present in liver and brain, exogenous εG was detected in liver only. Similar results were reported by Mutlu et al [62] for the formation of endogenous and exogenous εG in liver DNA (4.1±2.8 endogenous εG/10 8 G and 18.9±4.9 [ 13 C 2 ]-εG/10 8 G). In contrast, both endogenous 7-OEG and [ 13 C 2 ]-7-OEG were detected in several organs, including liver and brain in rats exposed to 1100 ppm [ 13 C 2 ]-VC [50] This suggests that not only liver, but the other organs are able to form low amounts of CEO, which results in lower [ 13 C 2 ]-7-OEG adduct formation, it is believed that VC is metabolized in each organ by CYP450, rather than arising via the circulation of higher liver-based CEO formation in the body.…”
Section: Vinyl Chloridesupporting
confidence: 91%
See 2 more Smart Citations
“…While endogenous εG was present in liver and brain, exogenous εG was detected in liver only. Similar results were reported by Mutlu et al [62] for the formation of endogenous and exogenous εG in liver DNA (4.1±2.8 endogenous εG/10 8 G and 18.9±4.9 [ 13 C 2 ]-εG/10 8 G). In contrast, both endogenous 7-OEG and [ 13 C 2 ]-7-OEG were detected in several organs, including liver and brain in rats exposed to 1100 ppm [ 13 C 2 ]-VC [50] This suggests that not only liver, but the other organs are able to form low amounts of CEO, which results in lower [ 13 C 2 ]-7-OEG adduct formation, it is believed that VC is metabolized in each organ by CYP450, rather than arising via the circulation of higher liver-based CEO formation in the body.…”
Section: Vinyl Chloridesupporting
confidence: 91%
“…In vivo formation of εG has been measured by GC-NICI-MS [5760], immunoaffinity coupled-GC/HRMS [45, 48, 49, 61] and LC-MS/MS [62]. Fedtke et al [59] reported the formation of εG that could not differentiate between endogenous and exogenous sources in rats exposed to 600 ppm VC for 5 days.…”
Section: Vinyl Chloridementioning
confidence: 99%
See 1 more Smart Citation
“…42 AcrdGuo, CrdGuo, and HNEdGuo standards and their 15 N 5 labeled internal standards were synthesized according to previous studies. 4345 7-OEG, 15 N 5 -7-OEG, and N 2 ,3-εG were synthesized as described previously by Mutlu et al 9,46 …”
Section: Methodsmentioning
confidence: 99%
“…46-48 It was previously reported that following VC exposure via inhalation (600 ppm, 4 h/day, 5 days), 7-OEG and εG concentrations in 10 day old rats were ~ 4-fold higher than lactating rats. 46 Age dependent differences in formation of εG by VC exposure were also studied by Morinello et al .…”
Section: Introductionmentioning
confidence: 98%